Katibah Nusantara : Islamic state’s Malay Archipelago combat unit - Singh, Jasminder (2015)
While the self-proclaimed Islamic State has been identified as a serious security threat worldwide, the establishment of the Katibah Nusantara, a dedicated Southeast Asian military unit within IS, is a new direct challenge to Southeast Asia.